Effect of processing methods on cyanogenic compounds, protein, and minerals of cassava leaves (Current Horticulture, 2024)
This study investigated the effects of boiling, drying, and ensiling on linamarin content, protein content, and mineral composition  of cassava (Manihot esculenta Crantz) leaves. The drying was found effective method for reducing linamarin content in most  genotypes. Boiling had variable effects, with some genotypes showing similar or slightly lower linamarin levels compared to  fresh leaves. Ensiling significantly reduced linamarin content after 7 days, with the reduction remaining stable up to 20 days,  indicating its effectiveness in reducing cyanogenic compounds. However, genotypes, H 1687 and Malayan 4, showed a decrease in  protein content during ensilage, suggesting potential nutritional changes. The study also observed dynamic changes in mineral  composition of cassava leaves, with copper, zinc, iron, and manganese varying over time. These findings highlight the impact of  different processing methods on nutritional quality of cassava leaves, emphasizing the need to consider these factors when using  cassava leaves as animal feed.
Keywords: Cyanogenic compounds; Genotype; Linamarin; Processing methods; Leaves